“Alexa, play today’s Flash Briefing”: utilizing conversational agents in educator preparation - Tiffany Hunt; Margaret Hudson (PDS Partners)
Purpose – This grant-funded research utilized conversational agents (CAs), specifically Alexa Flash Briefings, to deliver supplemental audio content across educational settings, expanding the online learning environment of graduate students, residency teachers and mentors. The study aimed to determine the perceived usability of Flash Briefings and explore participant experiences related to Flash Briefings. Design/methodology/approach – To explore Flash Briefing usability and participant perceptions, a review of relevant literature and researcher experience feedback was conducted. Additionally, graduate student feedback was sought via a modified Children’s Usage Rating Profile (CURP) Assessment survey, which also included questions related to listening habits and provided space for participants to share open-ended qualitative feedback. Data were analyzed for themes and descriptive statistics were calculated. Findings – Findings suggest an overall positive perception of the use of Flash Briefings. A mix of positive experiences and challenges are identified based on user population. The study provides valuable insights for refining the utilization of Flash Briefings in higher education settings. Research limitations/implications – Variable levels of participation across a small sample size minimizes the generalizability of the results and fails to explore perceptions of student teachers and mentors. Practical implications – The study offers an initial indication of benefits and challenges found in the implementation of an innovative technological intervention. Originality/value – There is a continued need and demand for extending online instructional accessibility and communication across broad geographic areas. This study considers a unique approach and provides a step toward closing this gap by analyzing the effectiveness this content modality offers in higher education.